2022
DOI: 10.1136/jitc-2022-005543
|View full text |Cite
|
Sign up to set email alerts
|

Anti-TGF-β/PD-L1 bispecific antibody promotes T cell infiltration and exhibits enhanced antitumor activity in triple-negative breast cancer

Abstract: BackgroundAgents blocking programmed cell death protein 1/programmed death-ligand 1 (PD-1/PD-L1) have been approved for triple-negative breast cancer (TNBC). However, the response rate of anti-PD-1/PD-L1 is still unsatisfactory, partly due to immunosuppressive factors such as transforming growth factor-beta (TGF-β). In our previous pilot study, the bispecific antibody targeting TGF-β and murine PD-L1 (termed YM101) showed potent antitumor effect. In this work, we constructed a bispecific antibody targeting TGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 53 publications
(56 reference statements)
0
51
0
Order By: Relevance
“…In this context, findings from studies suggest that the expression level of immune checkpoints strongly affects immunotherapy efficacy ( 39 ). Hence, immune checkpoint inhibitors are promising therapies for MTHFD2-mediated triple-negative breast cancer ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, findings from studies suggest that the expression level of immune checkpoints strongly affects immunotherapy efficacy ( 39 ). Hence, immune checkpoint inhibitors are promising therapies for MTHFD2-mediated triple-negative breast cancer ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of PD-1 and CTLA-4 blockers is associated with an increased incidence of adverse events, accompanied by severe myocarditis in some patients (44). Bintrafusp alfa, a bifunctional fusion protein consisting of the transforming growth factor b (TGFb) receptor fused to a human immunoglobulin G1 antibody that blocks programmed death ligand 1 (PD-L1), has been evaluated for safety and efficacy in patients with advanced NSCLC, breast cancer, and pancreatic cancer (45)(46)(47). Mitra et al administered TGF-b in combination with PD-L1 antibody to mice for 5 weeks and observed acute bleeding and cardiovascular toxicity (48).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that depending on the cell and cytokine configuration present in the TME, cancer cells are more or less responsive to immunotherapy, leading to the definitions of ''hot'' and ''cold'' tumors [26]. There are many targets directed toward tumor-associated immune and stromal compartments and of these, we highlight tumor growth factor (TGF)-beta, which has many immunosuppressive effects in the TME, by affecting the activities of tumor-infiltrating lymphocytes, macrophages, and regulatory T and dendritic cells and bispecific antibodies (targeting TGF-beta and PD-L1), such as YM101, BiTP, and M7824 [27][28][29].…”
Section: Overview Of the Clinical Evidencementioning
confidence: 99%